How to Monitor Cardiac Complications of Immune Checkpoint Inhibitor Therapy - Spallarossa, Paolo; Sarocchi, Matteo; Tini, Giacomo; Arboscello, Eleonora; Toma, Matteo; Ameri, Pietro; Porto, Italo (Frontiers in Pharmacology, 2020)
Immune-checkpoint inhibitors (ICIs) represent a successful paradigm in the treatment of cancer. ICIs elicit an immune response directed against cancer cells, by targeting the so-called immune checkpoints, key regulators of the immune system that when stimulated can dampen the immune response to an immunologic stimulus. Such response, however, is not entirely tumor-specific and may result in immune-related adverse events (irAEs), involving a number of organs and systems. Cardiovascular (CV) irAEs are rare, although potentially severe. In particular, several cases of ICI-related myocarditis with life-threatening course have been reported: the possibility of fulminant cases, thus, requires a high level of awareness among both oncologists and cardiologists. Aggressive work-up and management of symptomatic patients taking ICIs is fundamental for early recognition and initiation of specific immunosuppressive therapies. Notably, myocarditis occurs within few weeks from ICIs initiation, offering opportunity for a targeted screening. Troponin testing is the cornerstone of this screening, yet uncertainties remain regarding timing and candidates. Moreover, troponins positivity should be carefully interpreted. We herein review the main aspects of ICI-related myocarditis and suggest a practical approach. In particular, we focus on the opportunities that a baseline CV evaluation offers for subsequent management by collecting clinical and instrumental data, essential for the interpretation of troponin results, for differential diagnosis and for the formulation of a diagnostic and therapeutic workup.